Students’ Perception of the Role of Online Teachers:Comparing Routine and Emergency Times - Sason, Hava; Wasserman, Egoza; Safrai, Mordechai Zvi; Romi, Shlomo (Frontiers in Education, 2022)
Social distancing during the COVID-19 pandemic forced the education system to instantly transition to online learning and teaching. Studies show that the challenges of emergency remote teaching (ERT) differ from those of online learning during routine times. Do student's perceptions of teachers' roles during online learning differ between ERT and routine online classes as well? Addressing this question can illuminate different aspects of the role of a teacher at different times, thus facilitating the improvement of online learning. This study compares students' perceptions of their teachers' roles in the online courses they attended during the pandemic, with perceptions of students who attended online courses in routine times when distance learning was a regular part of the academic program. The participants who attended online courses during routine times were 520 undergraduates in a teacher-education college. A second group of 475 undergraduates from the same college responded at the end of a semester of emergency online learning during the pandemic. Both groups answered questionnaires regarding their perception of four aspects of the role of online teachers: pedagogical, technical, affective, and differentiating. The findings showed that during emergency times, students had significantly higher expectations for teachers' technical and affective roles than in routine times. However, students had lower expectations regarding teachers' differentiating role during emergencies, and similar expectations for teachers' pedagogical role in both situations. These findings highlight the need to plan curricula to suit different situations and different needs, and emphasize the different characteristics of the teachers' role in different situations, in order to optimally address students' needs in times of routine and emergency alike.